A karyological study of some Dianthus L. species (Caryophyllaceae) in Northeast of Iran. Issue 4 (20th January 2014) - Behroozian, Maryam; Vaezi, Jamil; Reza Joharchi, Mohammad
Abstract: This study focuses on karyological investigation of four taxa of Dianthus (Caryophyllaceae) including D. crossopetalus, D. orientalis subsp. stenocalyx, D. orientalis subsp. gorganicus, and Dianthus sp. distributed in Northeast of Iran. The karyotype asymmetry/symmetry was evaluated using two methods: 1) CVCL (coefficient of variation of chromosome length) and CVCI (heterogeneity of the centromeric index); and 2) MCA (mean centromeric asymmetry). The karyotype asymmetry was also used to investigate the relationships among the taxa. Results obtained from the current study revealed that there are two different ploidy levels (2 n = 2 x = 30 and 2 n = 4 x = 60) among the investigated taxa. The indices CVCL and MCA described karyotype asymmetry correctly based on variation in chromosome length. Diagram of CVCL vs. MCA seems to be appropriate for karyological delimitation and taxonomic relationships among the Dianthus taxa under study. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)